KEEFEKTIFAN SANDIWARA BONEKA UNTUK MEMBENTUK PERILAKU ASERTIF SISWA SEKOLAH DASAR - Robbi Suraida Utami; M. Ramli; Blasius Boli Lasan; Husni Hanafi (Bhinneka Tunggal Ika Journal, 2025)
Students developing task of having assertive behavior that can make them respond appropriately to things that harm themselves needed to be formed early on, that is when in low grade elementary school. Puppet plays are role playing techniques that have conformity in shaping assertive behavior in low grade elementary school students in the form of pleasant conditions presented during the service process. Tests carried out on 30 students at Muhammadiyah 4 Elementary School Malang showed evidence of a significant positive difference between the results of the students' pretest and posttest. Evidence of limited effectiveness suggests further testing using puppet theater techniques in shaping assertive behavior in elementary school students.